Cerebral Palsy and Leukomalacia in LBW Infants - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
Ultrasound findings and incidence of cerebral palsy in 24 infants < 2500 g with cystic periventricular leukomalacia are reported from Nagoya City University Med School, Japan.